Estimating bearing capacity using static cone penetration test at Banda Aceh area (northern tip of Sumatra). Issue 1 (February 2021) - Setiawan, B; Saidi, T; Sungkar, M; Gunawan, H; Yulianur, A; Zulkifli, Z; Malik, I
Abstract: The static cone penetration test (s-CPT), or better known in Indonesia as the sondir, has been used as a soil investigation procedure since nearly half a century ago in Europe, especially in the Netherlands and Belgium. This s-CPT is one of the standard practices in soil investigation campaigns and can provide many soil engineering parameters, including soil bearing capacity. This study focuses on the soil bearing capacity analysis in the city of Banda Aceh on the data taken from the 35 points of s-CPT. The analysis of the soil bearing capacity at a depth of 1.4 meters and 2.4 meters below the existing ground level (mbgl) was carried out. Dominantly, at a depth of 1.4 mbgl at the research location, it has a low bearing capacity (<2.5 tons/m 2 ) with a percentage of 91.43%. There are 2.86% for bearing capacity from 2.5 to 5 tons/m 2, from 5 to 7.5 tons/m 2, and from 7.5 to 10 tons/m 2 . No soil layer had a bearing capacity above 10 tons/m 2 . At a depth of 2.4 mbgl, the research location has a low bearing capacity (<2.5 tons/m 2 ) with a percentage of 48.57%, for bearing capacity ranging from 2.5 to 5 tons/m 2 is 17.14%, for bearing capacity of 5 to 7.5 tons/m 2 is 2.86%, for bearing capacity of 7.5 to 10 tons/m 2 of 5.71% and bearing capacity above 10 tons/m 2 is 25.71%.